Fluorescence imaging in evaluating the revascularization of heterotopically transplanted primate trachea segment - A. L. Akopov; G. V. Papayan; S. D. Gorbunkov; S. V. Orlov; D. D. Karal-Ogly; P. A. Kaplanyan; E. A. Gubareva; E. V. Kuevda; D. M. Kuznetsova (Вестник трансплантологии и искусственных органов)
Objective: to assess the potentials of using indocyanine green fluorescence angiography in evaluating revascularization of tissue-engineered construct that was obtained from the decellularized biological matrix of primate trachea, including using mesenchymal stem cells, after heterotopic tracheal allotransplantation. Material and methods. Tracheas were obtained from two male hamadryas baboons. After decellularization, 4 cm segments of tracheas were implanted under the lateral part of the latissimus dorsi in two healthy primates, one after recellularization with mesenchymal stem cells (animal 1), and the second without recellularization (animal 2). Immunosuppressive therapy was not performed. Blood flow in the transplanted segment of the trachea was evaluated 60 days after transplantation by surgical isolation of the flap of the latissimus dorsi with the transplanted segment of the trachea, while maintaining blood flow through the thoracodorsal artery. Indocyanine green near-infrared fluorescence angiography was visualized using a FLUM-808 multispectral fluorescence organoscope. Results. Sixty days after implantation, the tracheal cartilaginous framework macroscopically appeared to be intact in both animals, tightly integrated into the muscle tissue. The framework retained its natural color. After intravenous injection of indocyanine green, the tracheal vessels were visualized in both animals. Intercartilaginous vessels and portions of the cartilaginous semi-rings devoid of vessels were clearly distinguished. The entire implanted segment was almost uniformly vascularized. No local disruptions in blood supply were observed. The fluorescence brightness of the tracheal vessels was 193 ± 17 cu and 198 ± 10 cu in animals 1 and 2, respectively. The average muscle brightness in the implantation zone was 159 ± 9 cu and 116 ± 8 cu in animals 1 and 2, respectively. Conclusion. Indocyanine green fluorescence angiography is characterized by high-contrast images and high sensitivity. This facilitates vascular patency visualization and allows to assess the degree of neoangiogenesis after experimental transplantation of the tracheal segment, at different stages of experiment, without euthanizing the animal.